(untitled) (CIPEEX, 2022)
INTRODUCTION: HOMOSEXUALITY HAS BEEN DEBATED IN MANY WAYS, SEEN AS PHYSICAL ATTRACTION BY THE SAME-SEX PERSON. THE DEMAND FOR HEALTH CARE FOR MEN WHO HAVE SEX WITH MEN IS PRECARIOUS IN THE UNITS, BECAUSE THE VAST MAJORITY DO NOT ADAPT OR FEEL AFRAID OF SUFFERING SOCIAL DISCRIMINATION. OBJECTIVE: TO DESCRIBE THE EXPERIENCE OF MALE HOMOSEXUAL MEN FROM A CITY IN THE INTERIOR OF GOIS IN RELATION TO HEALTH CARE SERVICES. METHOD: A QUALITATIVE STUDY. FIFTEEN HOMOSEXUAL MEN PARTICIPATED IN THE STUDY. THE SAMPLE WAS RECRUITED RANDOMLY AND FOR CONVENIENCE USING THE SNOWBALL TECHNIQUE. THE SEMI-STRUCTURED INTERVIEW WAS USED TO COLLECT THE DATA. FOR DATA ANALYSIS, THE CONTENT ANALYSIS TECHNIQUE WAS ADOPTED (BARDIN, 2011). RESULTS: THE PARTICIPANTS’ MEAN AGE WAS 19 AND 27 YEARS. THE LAST TIME THEY SOUGHT THE HEALTH SERVICE WAS LESS THAN SIX MONTHS OR A YEAR. THE TYPES OF SERVICES SOUGHT WERE THE PUBLIC SERVICE, PRIVATE SERVICE OR BOTH. AS FOR THE PERIODIC EXAMINATIONS, THE PROMOTERS WERE THE FATHER, THE MOTHER, THE COMPANY THAT WORK OR THE FRIENDS. TWO CATEGORIES WERE IDENTIFIED: "HEALTH CARE ASSISTANCE", DIVIDED INTO TWO SUBCATEGORIES: "DIFFICULTIES IN ACCESS", "MULTIDISCIPLINARY TEAM AND ACTIONS IN HEALTH". THE DIFFICULTIES IN ACCESS WERE THE INEFFICIENCY OF THE SERVICE BY BUREAUCRACY, DELAY IN ATTENDANCE, LACK OF INTEGRAL CARE, FEAR OF DISCOVERING DISEASES AND PREJUDICE PRACTICED BY HEALTH PROFESSIONALS. AS FOR THE "MULTIPROFESSIONAL TEAM AND HEALTH ACTIONS", THEY REPORTED THAT THEY USED THE FAMILY HEALTH STRATEGY (FHS) SOMETIMES OR ONLY AS A CHILD, WHEN THEY HAD NOSE TRAUMA, DENGUE FEVER AND SUSPECTED STIS. NURSES, DOCTORS, DENTISTS, PSYCHOLOGISTS AND PHARMACISTS, BEING THE NURSE THE MOST EFFECTIVE IN THE CARE, ATTENDED THEM. THEY REPORT THAT THEY DID NOT PARTICIPATE IN HEALTH ACTIONS AIMED AT THE MALE HOMOSEXUAL POPULATION IN THE FHS. THE SECOND CATEGORY "MALE RESISTANCE" WAS DIVIDED INTO THREE SUBCATEGORIES: "DEHYDRATION AND DEMAND", "INDIVIDUAL RESISTANCE" AND "KNOWLEDGE OF THE NATIONAL POLICY ON COMPREHENSIVE HEALTH CARE FOR MAN (PNAISH)". THE INDIVIDUAL RESISTANCES WERE LACK OF TIME, LAZINESS, ECONOMIC FACTORS, FEAR OF HOSPITAL PROCEDURES, EXPOSURE OF THE BODY AND PREJUDICE IN CARE. AS FOR "DEHYDRATION AND DEMAND", THE REASONS THAT LED TO URGENCY AND EMERGENCY WERE: ACUTE MYOCARDIAL INFARCTION, INFECTIONS, PROSTATE DISEASE, DYSPNEA, APPENDICITIS, CONJUNCTIVITIS AND TONSILLITIS. REGARDING THE "KNOWLEDGE OF PNAISH", MOST OF THEM KNOW SUPERFICIALLY THE PNAISH, BEING ASSOCIATED WITH THE BLUE NOVEMBER WITH ACTIONS DIRECTED TO PROSTATE CANCER. CONCLUSION: THERE IS A NEED TO REFLECT EVEN MORE ON HUMAN HEALTH, REGARDLESS OF SEXUAL ORIENTATION. IT IS IMPERATIVE THAT NURSES WORK IN PRIMARY CARE AND EVEN IN EMERGENCY AND EMERGENCY SERVICES, WITH THE DEVELOPMENT OF ACTIONS FOR THE ADHESION OF THESE MEN TO THE HEALTH SERVICE IN A PREVENTIVE AND NON-CURATIVE VIEW. WE EMPHASIZE THE IMPORTANCE OF FURTHER STUDIES ON THE SUBJECT, SINCE IT IS BROAD AND COMPLEX AND LITTLE EXPLORED WHEN COMPARED TO WOMEN’S HEALTH.